Regression equations for stature reconstruction from the lower limb bones of contemporary White South Africans - Bidmos, Mubarak A.; Loubser, Natasha; Brits, Desiré (Australian journal of forensic sciences, 2024)
In 2008, Dayal and colleagues generated regression equations to estimate the total skeletal height (TSH) of White South Africans. However, the validity of these equations has been questioned. The magnetic resonance imaging scanograms of 74 White South African adults were used to assess the reliability of these equations. The physiological lengths of the femur (FEPL) and tibia (TPL) were measured from these scans and input into the appropriate equations by Dayal and colleagues to calculate TSH D . Paired t-tests, mean differences (MD), and mean absolute differences (MAD) were used to compare TSH D with the measured TSH (TSH Meas ) taken directly from the scanograms and ELS were compared with the measured stature (LSM) taken of participants prior to their scans. Although there were no significant differences between TSH Meas and TSH D for males and TSH Meas and TSH D (TPL) for females, all ELS L were significantly different to LSM, and the ELS C using the FEPL were significantly different to LSM. These significant differences and associated large MD and MAD conclude that the equations by Dayal and colleagues are no longer valid. New stature estimation equations were derived for the estimation of stature of White South Africans, characterized by strong correlations and low SEEs.